A 1Mbps Real-Time NLOS UV Scattering Communication System With Receiver Diversity Over 1km - Guanchu Wang; Kun Wang; Chen Gong; Difan Zou; Zhimeng Jiang; Zhengyuan Xu (IEEE Photonics Journal)
In the nonline of sight (NLOS) ultraviolet (UV) scattering communication, the received signals exhibit the characteristics of discrete photoelectrons due to the extremely large path loss. We design and demonstrate an NLOS UV scattering communication system in this paper, where the receiver-side signal detection is designed based on a discrete-time Poisson channel model. In our system, a laser and multiple photomultiplier tubes are employed as the optical transmitter and detector, respectively. Furthermore, we design algorithms for pulse-counting, synchronization, channel estimation, and ${\rm{LLR}}$ computation for hardware realization in field-programmable gate array board. Simulation results are provided to evaluate the proposed system design and specify the system key parameters for real-time implementation. We perform field tests for real-time communication with the transmission range over 1 km, where the system throughput reaches 1 Mbps.